MEMAKNAI SUMPAH DALAM PERATURAN PRESIDEN REPUBLIK INDONESIA NOMOR 61 TAHUN 2018 TENTANG SUMPAH JABATAN PANGLIMA TENTARA NASIONAL INDONESIA, KEPALA KEPOLISIAN NEGARA REPUBLIK INDONESIA, DAN KEPALA STAF ANGKATAN - Michael, Tomy (Yayasan Akrab Pekanbaru, 2019)
In the Decree of the People's Consultative Assembly of the Republic of Indonesia Number: VI / MPR / 2001 concerning the Ethics of National Life (TAP MPR No. VI / 2001), it was explained that the Indonesian Nation was created by Allah, the Almighty God, as a plurality based on ethnicity, culture, race and religion. Appearance Presidential Regulation No. 61-2018 and its consideration that Indonesian National Army Officers and Indonesian National Police Officers who will be in the position of Commander of the Indonesian National Army, Indonesian National Police Chief, and Force Chief of Staff, must swear at the inauguration. Its legal problems are in Article 3 of Presidential Regulation No. 61-2018 which are limited in nature. Presidential Decree No. 61-2018 contradicts the spirit of the Pancasila even though it has arranged for those who believe in God Almighty besides Islam, Christianity, Hinduism, Buddhism, and Confucianism, the phrase For Allah is replaced with another sentence.